Quality of life among patients with ureteric stents and its associated symptoms in urology clinic, Hospital Universiti Sains Malaysia - Din, Hazrita Mat (Universiti Sains Malaysia, 2016)
Placement of indwelling ureteric stents is one of the most common urological procedures in current endourology, and often is associated with effect on quality of life (QOL). The objective of this study was to evaluate the QOL among patients with ureteral stents and the symptoms associated with ureteral stents in Hospital Universiti Sains Malaysia (Hospital USM). A cross sectional study of 82 adult patients with indwelling ureteral stents were invited to participate in this study using a selfadministered urinary stent symptoms questionnaire (USSQ) sampled by purposive sampling. Majority of the participants were Malay (95. l %) and mean age was 53.88 (SD 12.64). Results revealed a significant difference in mean USSQ score between gender (p = 0.00 I), marital status (p = 0.003), educational level (p = 0.003) and number of stent change (p = 0.00 l) based on time of stent changes when age is controlled. Urinary symptoms and pain that affected work performance and general health were important stent related problems. Of the patients, 98.7% reported bothersome urinary symptoms that included storage symptoms, incontinence, and hematuria; while 32% of patients experienced stent related pain affecting daily activities. Of the 82 patients, 29.3% reported no sexual life and among these patients, 9 (37.5%) was due to the problem associated with stents. Mean days of work performance affected where patients keep in bed most of the day were 5.5 days. It can be concluded that indwelling ureteral stents are associated with a range of urinary tract symptoms and pain; and have a significant impact on health related quality of life. The urgent concerted effort by healthcare professionals and the Ministry of Health Malaysia authorities to educate patients experienced stent related pain and severe urinary symptoms and to improve their health seeking behavior is needed.